SURVEI KINERJA GUDANG DENGAN MENGGUNAKAN METODE TECHNOMETRIC DI KOTA PONTIANAK - -, WAHYUNI - (Jurnal TIN Universitas Tanjungpura, 2017)
Consumer good warehouse is a company which acts to distribute mass consumption products, either foods or other goods. Nowadays, warehousing in Pontianak City is developing rapidly, but the fact that the warehouse performance profile is still nowhere near available, making the consumer to look for the information of the warehouse they need all by themselves. This research is aimed to acquire informations about warehouse performance profile in Pontianak and detect the level of their application in technology. The research is conducted in five companies, from Warehouse A to Warehouse E using single-tour survey to obtain the needed data and then processing the data using technometric approach. The result of this research is the value of technology contribution in each companies. Warehouse A in technoware component is 0.47, its humanware component is 0.57, infoware component is 0.47 and orgaware is 0.59. the contribution of technoware component in Warehouse B is 0.47, humanware 0.86, infowareÂ 0.75, and orgaware 0.76. The contribution of technoware in Warehouse C is 0.80, its humanware is 0.55, infoware contribution is 0.56, and the orgaware is 0.64. The contribution of technoware component in Warehouse C is 0.7, humanware 0.62, infoware 0.66, and orgaware 0.68. The contribution of technoware in Warehouse D is 0.62, humanware 0.72, infoware 0.61, and orgaware 0.63. The outcome of CCT (Contribution Coefficient Technology) for Warehouse A is 0.58, Warehouse B is 0.77, Warehouse C is 0.61, Warehouse D is 0.66, and 0.65 for Warehouse E. If we categorize them on qualitative assessment scale, the only warehouse having a good rating is Warehouse B as it is placed one level above any other warehouses, which is rated to be very good. Keyword: Consumer Goods Warehouse, Single Tour, Technometric